Assessing the influence of researcher–partner involvement on the process and outcomes of participatory research in autism spectrum disorder and neurodevelopmental disorders: A scoping review. (October 2014) - Jivraj, Jamil; Sacrey, Lori-Ann; Newton, Amanda; Nicholas, David; Zwaigenbaum, Lonnie
Participatory research aims to increase the relevance and broaden the implementation of health research by involving those affected by the outcomes of health studies. Few studies within the field of neurodevelopmental disorders, particularly autism spectrum disorders, have involved autistic individuals as partners. This study sought to identify and characterize published participatory research partnerships between researchers and individuals with autism spectrum disorder or other neurodevelopmental disorders and examine the influence of participatory research partnerships on the research process and reported study outcomes. A search of databases and review of gray literature identified seven studies that described participatory research partnerships between academic researchers and individuals with autism spectrum disorder or other neurodevelopmental disorders. A comparative analysis of the studies revealed two key themes: (1) variations in the participatory research design and (2) limitations during the reporting of the depth of the partner's involvement. Both themes potentially limit the application and generalizability of the findings. The results of the review are discussed in relation to the use of evaluative frameworks for such participatory research studies to determine the potential benefits of participatory research partnerships within the neurodevelopmental and autism spectrum disorder populations.